An Autopsy Case of Spontaneous Splenic Rupture Due to Isolated Splenic Peliosis and Review of the Literature. Issue 2 (June 2016) - Prats, Mariana Moreno; Aronson, Judith F.
Peliosis is a rare entity that is characterized by cystic or blood-filled spaces in the parenchyma of solid organs. It is most commonly seen in the spleen in patients who also have peliosis hepatis. Isolated splenic peliosis is very rare and spontaneous rupture due to splenic peliosis is even more uncommon. This diagnosis has high importance in forensic pathology as it is a rare cause of atraumatic splenic rupture. We present a case in which the diagnosis of isolated splenic peliosis with massive hemoperitoneum was made at autopsy.